2003
DOI: 10.1557/jmr.2003.0219
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced field emission from nitrogen-doped amorphous diamond

Abstract: Undoped and nitrogen-doped amorphous diamond were deposited on n-type Si(100) substrate by a cathodic arc process. By varying nitrogen partial pressure of the gas mixture in the range of 0 to 55.6%, up to 23 at.% of nitrogen was incorporated in amorphous diamond. The electron spectroscopy for chemical analysis, Raman, and atomic force microscopy measurements indicated that most nitrogen atoms replaced carbon atoms in the amorphous structure. The electron concentration, mobility, and its resistivity were determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In addition, the emission current density was significantly increased by plasma treatment. 23,24 Hence, we strongly suggest that the enhanced field emission characteristics of ZnO nanoneedles after hydrogen plasma treatment result from the increased carrier concentration due to hydrogen doping. The hydrogen doping effect was also investigated measuring low temperature ͑10 K͒ PL spectra of ZnO nanoneedle array before and after hydrogen-plasma treatment.…”
Section: Fig 3 Field Emission Characteristic Curves Of As-grown Andmentioning
confidence: 87%
“…In addition, the emission current density was significantly increased by plasma treatment. 23,24 Hence, we strongly suggest that the enhanced field emission characteristics of ZnO nanoneedles after hydrogen plasma treatment result from the increased carrier concentration due to hydrogen doping. The hydrogen doping effect was also investigated measuring low temperature ͑10 K͒ PL spectra of ZnO nanoneedle array before and after hydrogen-plasma treatment.…”
Section: Fig 3 Field Emission Characteristic Curves Of As-grown Andmentioning
confidence: 87%
“…Gaussian spectral decomposition (Gaussian fitting) revealed that the broadened spectrum can be decomposed into five constituents centered at 284.4 ± 0.3 eV, 285.4 ± 0.3 eV, 286.4 ± 0.3 eV, 288.1 ± 0.3 eV, and 289.5 ± 0.3 eV. Thus the carbon 1s peak measured by ESCA could contain C\C sp 2 , C\C sp 3 , C\N sp 2 , C\N sp 3 , and C\O bonds [52].…”
Section: Post-treatment Using Various Nitrogen Concentrationsmentioning
confidence: 98%